Potencialidades para un turismo sostenible en el Marruecos meridional - Humbert, André (Geographicalia, 2014)
If Morocco receives tourists interested in the visit of its “imperial cities”and its souks, the country also has a deposit of an extraordinary wealth in the countryside of the Atlas mountains in the South. It not only offers the exotism of its natural mountain landscapes and desert but also all the objects or buildings of an old agrarian civilization adapted to the dryness and the relief. The non exhaustive inventory of the offered patrimonial resources allows to consider the possibilities of a considerable development for a sustainable cultural tourism that benefits to an ample underprivileged region by the desertion of great part of its active forces. A circuit of real cultural tourism is proposed like example and test of the feasibility of an activity that allows to mitigate the imbalances of the country.